Efficient and Reusable Metal Heterogeneous Catalysts for Conversion of CO2 Prepared from a Microwave Synthetized Porous Polyiminopyridine. Issue 29 (18th October 2017) - Maya, Eva M.; González‐Lucas, María; Iglesias, Marta
Abstract: A stable nitrogen‐rich porous polyimine containing pyridine units (PIPy‐4Mw ) was successfully synthesized under microwave heating via a simple "one‐step" polycondensation in only 30 min without adding any catalyst. This versatile polymer can incorporate different transition metals leading polyiminopyridine‐supported catalysts; in this paper we report the synthesis and catalytic performance of heterogenized complexes of abundant earth metals such as iron(II), cobalt(II) and chromium(III) (PIPy‐4MwFe, PIPy‐4MwCo andPIPy‐4MwCr ). These supported metal‐polyiminopyridines have been applied as heterogeneous catalysts in the conversion of CO2 into cyclic carbonates, an interesting reaction to recycle CO2, and in another eco‐friendly reaction: the synthesis of additives for diesel fuels by acetalization of furfural. The cobalt and iron complexes have showed high efficiency and were reused without any significant change in their activities. Abstract : A porous polyimine containing pyridine units (PIPy‐4Mw) was easily synthesized in 30 min under microwave heating and heterogenized complexes of abundant earth metals (PIPy‐4MwFe, PIPy‐4MwCo and PIPy‐4MwCr) were prepared and applied in the conversion of CO2 into cyclic carbonates and in the synthesis of additives for diesel fuels. The cobalt and iron complexes have showed excellent performance with high efficiency and reciclability.